Determination of Eugenol Contents of Some Zinc Oxide-Eugenol Based Dental Cements¶ - ERTAS, ERTAN; AKSOY, ABDURRAHMAN; GUVENC, DILEK; KURSAD DAS, Y.; CAGIN YUCEL, A. (Asian Journal of Chemistry, 2010)
The aim of this study was to analyze the eugenol content of some eugenol based commercially available dental cements. Eugenol analysis was made by gas chromatography equipped with flame ionization detector (GC-FID) and also results confirmed by gas chromatography-mass spectrometry (GCMS). In all products, eugenol was found in different concentrations. It is noteworthy that there were variations in the concentration of eugenol even in products manufactured by the same company. Due to the fact that anaesthetic, sedative and analgesic effects are related to the eugenol concentration. It is critical to have eugenol content standardized.